Pleomorphic undifferentiated soft tissue sarcoma in patient with long standing inflammatory bowel disease - Loredana Labinac-Peteh; Robert Terlević; Božo Krušlin (University of São Paulo, 2018)
Inflammatory bowel disease (IBD) has been associated with the development of both gastrointestinal and extraintestinal malignancy. The role of therapy in the development of malignancy in IBD has been controversial. We present the case of a 40-year-old female patient with long-standing mild IBD, who developed an undifferentiated pleomorphic sarcoma of the inguinal region and provide a brief review of the relevant literature. While our case likely represents a coincidence of two unrelated pathological entities, clinicians should keep in mind the possibility of soft tissue sarcomas in patients chronically treated with anti-inflammatory agents.